2020
DOI: 10.3390/catal10060620
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective ROP of rac- and meso-Lactides Using Achiral TBD as Catalyst

Abstract: 1,5,7-Triazabicyclo[4.4.0]dec-5-ene (TBD) polymerizes rac-lactide (rac-LA) to form highly isotactic polylactide (PLA) with a Pm = 0.88, while meso-LA yields heterotactic PLA (Pm ~ 0.8) at −75 °C. The stereocontrol of the cryogenic-based ring-opening polymerization comes from a perfect imbrication of both chiral LA and the propagating chiral end-group interacting with the achiral TBD catalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 25 publications
2
13
0
1
Order By: Relevance
“…In addition, evidence of a small amount of cyclization product was also detected by MALDI-TOF mass analysis. The regular m/z = 72 difference between the peaks indicated that significant transesterification took place during the polymerization process, which is consistent with TBD [25]. However, in some cases, transesterification could be used as well.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…In addition, evidence of a small amount of cyclization product was also detected by MALDI-TOF mass analysis. The regular m/z = 72 difference between the peaks indicated that significant transesterification took place during the polymerization process, which is consistent with TBD [25]. However, in some cases, transesterification could be used as well.…”
Section: Resultssupporting
confidence: 78%
“…However, to obtain stereocontrolled PLAs with TBD, cryogenic conditions were required ( P m = 0.58 at 23 °C 0.80 at –75 °C) to control the insertion of the monomer and reduce the side reaction (transesterification and epimerization reaction, etc.) [ 25 ]. Sterically crowded catalysts with a chiral center offer highly stereoselective polymers in the aforementioned organocatalysts for the stereoselective ROP of rac -LA.…”
Section: Introductionmentioning
confidence: 99%
“…A primary strategy for the construction of well-defined glucose-based polycarbonates has involved controlled ROPs . The guanidine organocatalyst, TBD, has been applied widely for the ROP for a variety of cyclic monomers in the presence of alcohol or amine initiators, while exerting high reactivity and excellent control of polymer molar mass and dispersity. More recently, regioselectivity has been observed using TBD during the ring-opening of cyclic carbonates and sugar-based fused-cyclic monomers. , Despite the importance of regiochemistry in directing synthesis, regulating properties, and thereby affecting polymer performance and applications, studies have seldom focused on revealing the regiochemical structures of the complex glucose-based polymers.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, chiral organocatalysts including binaphthol‐type phosphoric acids, [107] or a β‐isocupreidine/thiourea/chiral binaphthylamine, [108] have also been investigated. In a more recent report, Columbier et al., reported the ability of achiral TBD to produce greatly isotactic PLA from rac ‐LA at −75 °C [109] . Both chiral and achiral catalysts showed excellent stereocontrol; however, the ROP reactions are generally conducted at low temperatures which limits their use.…”
Section: Burgeoning Areas In Organocatalyzed and Other Transition‐met...mentioning
confidence: 99%